2013
DOI: 10.1016/j.jcin.2013.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Routine Assessment of On-Clopidogrel Platelet Reactivity and Gene Polymorphisms in Predicting Clinical Outcome Following Drug-Eluting Stent Implantation in Patients With Stable Coronary Artery Disease

Abstract: CYP2C19 metabolizer status is an independent predictor of MACE after DES implantation and can be used for prognostication in all stable CAD patients. High OTR, as assessed by the VerifyNow P2Y12 test, is an independent predictor of MACE only for high-risk subsets, that is, patients with diabetes or chronic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 45 publications
0
39
1
1
Order By: Relevance
“…We also specifically analyzed the relationship between genetic polymorphisms with HTPR and MACEs, but could not demonstrate any association between the two. Our results are in disagreement with those reported by Viviani Anselmi, et al 39) which suggested that polymorphisms in the CYP2C19 gene were an independent predictor of MACEs after drug eluting stent (DES) implantation and can be used as a prognostic tool to determine the stability of CAD patients. Several possible reasons could explain the lack of association between HTPR and MACEs in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…We also specifically analyzed the relationship between genetic polymorphisms with HTPR and MACEs, but could not demonstrate any association between the two. Our results are in disagreement with those reported by Viviani Anselmi, et al 39) which suggested that polymorphisms in the CYP2C19 gene were an independent predictor of MACEs after drug eluting stent (DES) implantation and can be used as a prognostic tool to determine the stability of CAD patients. Several possible reasons could explain the lack of association between HTPR and MACEs in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, nearly half of patients with acute coronary syndromes who underwent percutaneous intervention are genotype carriers associated with increased risk of MACE while on standard doses of clopidogrel [20]. In short, there is a mutual agreement that genetic biomarkers may serve as an independent predictor of MACE after stenting in patients treated with clopidogrel [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been implicated to be responsible for interindividual differences such as drug absorption and variability in drug metabolism, and genetic polymorphisms (GP) of the P2Y12 receptor have been reported to increase ADP-induced platelet reactivity [4][5][6]. Since thienopyridines are metabolized by liver enzymes, there is a potential link between CYP2C19 GP and variability of antiplatelet potency in certain carriers [7][8][9][10]. However, while conventional clopidogrel is always a "prime suspect" of such shortcoming [11][12][13], prasugrel is mostly overprotected, claiming superiority or at least lack of impact due to fewer metabolization steps required than older thienopyridines.…”
Section: Introductionmentioning
confidence: 99%
“…CYP1A2, CYP2B6, CYP2C9, CYP3A4 and CYP3A5) are also necessary for active clopidogrel metabolite formation, and all of these genes have known variant alleles. Some candidate gene studies identified significant effects on clopidogrel response (pharmacodynamic or clinical outcomes) with germline variants in CYP1A2 (with possible smoking interaction) [133, 134], CYP2C9 [68, 98, 135137], CYP3A4 [138, 139], and CYP3A5 [140, 141]; however, the majority of clinical clopidogrel pharmacogenetic studies have not confirmed a significant independent role for these other CYP450 genes [61, 71, 72, 77, 80, 93, 142145]. …”
Section: Clopidogrel Pharmacogeneticsmentioning
confidence: 99%